2012
DOI: 10.1123/ijatt.17.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Reaction Time Predicts Lower Extremity Sprains and Strains

Abstract: Context:Prevention of a lower extremity sprain or strain requires some basis for predicting that an individual athlete will sustain such an injury unless a modifiable risk factor is addressed.Objective:To assess the possible existence of an association between reaction time measured during completion of a computerized neurocognitive test battery and subsequent occurrence of a lower extremity sprain or strain.Design:Prospective cohort study.Setting:Preparticipation screening conducted in a computer laboratory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 18 publications
3
92
1
Order By: Relevance
“…57,58 The alterations in knee mechanics under SVFD indicate that lower extremity landing movement control may be influenced by the amount of visual feedback. Our data further supported the role of visual-motor function on landing motor control; specifically, visual feedback may provide a larger input to sustain sagittal-plane neuromuscular control after ACL injury.…”
Section: Kineticsmentioning
confidence: 99%
“…57,58 The alterations in knee mechanics under SVFD indicate that lower extremity landing movement control may be influenced by the amount of visual feedback. Our data further supported the role of visual-motor function on landing motor control; specifically, visual feedback may provide a larger input to sustain sagittal-plane neuromuscular control after ACL injury.…”
Section: Kineticsmentioning
confidence: 99%
“…18 As many as 50% of SRCs go unreported at the high school level, 1,8 leaving student-athletes vulnerable to another SRC or musculoskeletal injury due to postural instability or decreased neurocognitive function. [19][20][21] Raising awareness of SRCs and improving SRC knowledge is critical, yet these outcomes do not guarantee changes in attitudes and reporting behaviors. 1,7,10,22 The few investigators 1,7 who have empirically evaluated reasons why high school athletes would not report an SRC to an authoritative figure indicated that the athletes did not think the injury was serious enough to warrant medical attention, had fear of being removed from play, lacked awareness of a likely SRC, and did not want to let their teammates down.…”
mentioning
confidence: 99%
“…An ROC curve for discriminating injured football players (ie, those who ultimately sustained a core or lower extremity strain or sprain) from uninjured players on the basis of neurocognitive reaction time is presented in Figure 1. 33 Although the area under the curve is relatively small, a clearly definable point provided the basis for a binary classification of exposure status that produced evidence of a meaningful association with injury occurrence (Table). An inverse relationship (ie, fewer injuries among players with prolonged reaction time) would have produced an inverted ROC curve.…”
Section: Bayesian Approach To Observational Data Analysismentioning
confidence: 99%